2020
DOI: 10.1111/bjir.12556
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Organizational Factors in Mobilizing Professionals: Evidence from Nurse Unions in the United States and Germany

Abstract: Scholars have intensely debated the conditions under which trade unions can successfully mobilize professionals. We explore an internationally comparative perspective on mobilizing professionals by asking how two nurse unions in the United States and Germany successfully limited management's prerogative over staffing levels. We found that German national institutions had little influence over the bargaining process; instead, factors at the level of organizations and their environment (leadership support, organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…Her research suggests that identity can be an important factor informing more effective management practice. Ranganathan’s study also resonates with recent research on the mobilization around professional identity to improve job security and conditions (Rothstein 2019; Krachler, Auffenberg, and Wolf 2020).…”
Section: The Need For New Perspectivessupporting
confidence: 58%
“…Her research suggests that identity can be an important factor informing more effective management practice. Ranganathan’s study also resonates with recent research on the mobilization around professional identity to improve job security and conditions (Rothstein 2019; Krachler, Auffenberg, and Wolf 2020).…”
Section: The Need For New Perspectivessupporting
confidence: 58%
“…While the intent of this article is not to fully examine the impact of devolutionary-style policy in schools (for fuller coverage see Gavin and McGrath-Champ, 2017), analysis of the Scott Review and LSLD reforms illustrate how evolving discursive framing of similar devolutionary policies can enable, or indeed limit, the mobilisation of traditional power resources and weaken resistance against governance agendas. While organisational factors at the level of the union and its (potential) external coalition partners provide enabling conditions for mobilising professionals as unionists (Krachler et al, 2021), our study shows that aligning these approaches becomes more difficult when organisational counter-framing occurs around the interests of professionals and the public. This scenario prompts broader critical evaluation of mobilising union power in a neoliberal environment.…”
Section: Discussionmentioning
confidence: 83%
“…While militancy may still be appropriate under certain conditions (McAlevey 2016), it does invoke the need to understand the complexity and limitations on public sector unions in mobilising traditionally strong power resources. For instance, Krachler et al (2021) argue that unions can mobilise professionals with militancy by successfully combining employee-focused (i.e. as a trade union) or professional-focused (i.e.…”
Section: Union Power In the Public Sectormentioning
confidence: 99%
“…Researchers have countered such perspectives by examining how nurses often protect their professional values through acts of resistance and collective action. These studies have shown how nurses seek institutions where their “voices” are heard and where leaders recognize their professional values ( Traynor and Buus, 2016 ; Krachler et al, 2021 ). While these studies subvert the stereotype of nurses as self-sacrificing professionals, they do not entirely explain why some choose to enter institutions already notorious for treating nurses so poorly.…”
Section: Professionalism and Work Commitmentmentioning
confidence: 99%